THE PORTRAYAL OF THE FEMALE PROTAGONIST IN DARREN ARONOFSKY’S BLACK SWAN USING FREUD’S PSYCHOANALYTIC THEORY OF PERSONALITY AND DEFENSE MECHANISMS - Nastiti, Anisa Efani Yulandara; Sutandio, Anton (Capture : Jurnal Seni Media Rekam, 2023)
Black Swan is a psychological horror movie by Darren Aronofsky. This movie tells of a ballerina named Nina Sayers, who desires to be a perfect ballerina. On her way to achieving her desire, Nina experiences psychological problems where she often hallucinates and even hurts herself. It results from Nina’s anxiety that causes her to be afraid that her desire will not be fulfilled. This article aims to examine Nina’s psychological state during the process of achieving her dreams. To reveal the psychological issues experienced by Nina, a characteristic analysis was carried out using Sigmund Freud’s theory of psychoanalysis, the theory of human defense mechanisms, and the cinematographic aspects of this film. The results showed that uncontrolled desires could cause psychological disorders that influence a person’s characteristics.